Upaya Memakmurkan Masjid Pada Masyarakat Urban Melalui Program Sahabat Masjid Yayasan Nurul Hayat Surabaya - Saeful Anam; Khusnan Iskandar (Qolamuna : Jurnal Studi Islam, 2019)
This article explaian about the program of Nurul Hayat Foundation his name Sahabat Masjid. This study was designed with a descriptive qualitative approach. Data analysis used is descriptive by describing data that has been reductively selected and drawing phenomena that occur by understanding based on existing theories. The results of the study show, the first; that program sahabat masjidis one of the pioneers of enlivening and prospering the mosque, where the presence of this program is able to motivate the surrounding community to be active again in worship and participate in fervent droves in following the routine of recitation which is held. Second: the form of activities is not only worship but also social or economic activities organized by the mosque. Keyward: Sahabat Masjid, Urban Communities